Analisis Efisiensi Perusahaan Asuransi Umum dan Reasuransi Syariah di Indonesia Menggunakan Metode Data Envelopment Analysis - Elsi Dwijayanti; Dimas Sumitra Danisworo; Hasbi Assidiki Mauluddi (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the level of efficiency in Sharia Non Life Insurance and Reinsurance Business in Indonesia using the Data Envelopment Analysis (DEA) method. The data used in this study are the financial statements of all Sharia Non Life Insurance and Reinsurance Business in Indonesia for the 2015-2019 period published by the Financial Services Authority in Indonesian Insurance Statistics every year (2015-2019). There are two variables used in this study, namely the input variable which includes capital, other operating expenses, general and administrative expenses, and marketing expenses and the output variable, namely gross contribution. The results of this study are Sharia Non Life Insurance and Reinsurance Business in Indonesia in Indonesia in 2015 had an efficiency level or efficiency value of 87%, in 2016 and 2017 the efficiency level was 100%, in 2018 it was 95% and in 2019 it was 84%.